Management of double aortic arch in children - Samia Belhassen; Lassaad Sahnoun; Saloua Ammar; Amine Ksiaa; Rachida Laamiri; Mongi Mekki; Imed Krichene; Mohsen Belghith; Nouri Abdellatif (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2016)
Introduction: Double aortic arch (DAA) is a rare congenital malformation. Strategies for diagnosis and treatment are different. Reports of thoracoscopic treatment of DAA are rare. We report a description of our diagnostic and therapeutic approach and evaluate outcomes. Material & Methods: We reviewed charts of infants with double aortic arch who were hospitalized in our department from 2008 to 2014. Age at symptom onset, clinical presentation, diagnostic modality, operative details and post operative outcomes were retrieved.  Results: We identified 7 patients presenting at a median age of 11,8 months (range: 2 months-27 months) and median weight of 10kg. Respiratory symptoms were present in all cases. Difficulties in feedings were present in 3 cases. Chest radiography, oesophagogram and Computed Tomography (CT) with three-dimentional (3D) reconstructions were performed for all patients. One patient had laryngo tracheoscopy and 3 patients echocardiography. The dominant branch was the right one in all cases. Associated cardiac anomaly was found in 1 case. Operative approach was thoracotomy in 3 cases and thoracoscopic video assisted surgery (VATS) in 4 cases. Median operative time was 132 min. Only one patient required conversion. Median hospital stay was 4,1 days. Conclusion: Double aortic arch is a rare malformation which can cause persistent non specific respiratory symptoms in infants. The use of 3D-CT scan reconstruction facilitates diagnosis and the operative approach. Thoracoscopy and thoracotomy are effective procedures even for patients with low body weight. The operative time seems similar for both approaches. Thoracoscopy offers less post-operative analgesia requirement, shorter hospital stay and good cosmetic results.